KISAH ADIPATI JAYAKUSUMA-PANEMBAHAN SENOPATI DALAM HISTORIOGRAFI BABAD - Sudrajat Sudrajat (Universitas Negeri Yogyakarta, 2008)
AbstractThis research is to elaborate the relationship between Adipati Jayakusuma from Pati and Panembahan Senopati from Mataram. Regarding historians give little attention to solve this mysterious theme, we like to do research about it.This research uses historical method involving four steps that are: heuristic, critics, interpretations and historiography. We use babad as primary source of research in which Babad Pati to compare with Babad Tanah Jawi and other sources. We know that babad has several methodological weaknesses such as spatial, temporal, and factual. Regarding little writing sources, we have opinion that babad is one of solution to work away at problem. Despite, our work is not a history but a story; we wish invite for historians to begin analytical work for affect this course.From our research, we conclude that Adipati Jayakusuma and Panembahan Senopati have a brotherhood relationship. Adipati Jayakusuma is old brother because her sister is Panembahan Senopati’s wife. For the other hand their ancestor has brotherhood relationship. But we can’t tell anything that they were combat to kill one and, another. Babad Pati gives us informations that combating between Adipati Jayakusuma and Panembahan Senopati has two causes. First, misunderstanding about nonattendance Adipati Jayakusuma to meeting with her on Mataram Palace. Second, dissastified accumulation of Adipati Jayakusuma exclusively about exchange Juru Taman horse and Pragola cow, and the accomplish of Panembahan Senopati to married with Madiun princess. Finally, these causes lead for two prince from Pati and Mataram to combating one by one in Prambanan (Babad Tanah Jawi) or Kemalon (Babad Pati). But after Adipati Jayakusuma die, Mataram Prince dissatisfied in her heart caused for her misunderstanding.Keywords: Adipati Jayakusuma, Panembahan Senopati, Babad Pati, Babad Tanah Jawi.